Understanding Life and Death Meaning through the Character of Edna Pontelier in Kate Chopin's The Awakening - Elin Eprilin Fitrian Miela Putri (Universitas Gadjah Mada, 2023)
A character is a significant part in a tale who has its own personality or traits. Some variables, such as genes and environment, impact the development of a character's personality. Though Psychological approach, the researcher examines the personality development of the main character of Edna Pontellier in Kate Chopin’s The Awakening. From analyzing the character development, the researcher finds that the character of Edna Pontellier has changed and developed from being acceptance toward herself and her life to be rebellious in the search of her independence. The development of Edna’s character also changes the point of view of life and death. Edna feels happy, but in contrast, she feels something missing in her life. Edna feels that she does not belong to any community. She also feels that the world does not support her. That is one of the reasons why she chooses death as a way to find another happiness.